Analisis Pengaruh Belanja Pendidikan, PDRB Per Kapita, Jumlah Sekolah dan Jumlah Guru Terhadap Angka Partisipasi Jenjang Pendidikan Dasar di Provinsi Sulawesi Selatan - Ramli, Bustan; Aliah, Khaerunnisa; Iwang, Baso; Rusydi, Bahrul Ulum; Amar, Raja; Umar, Mustofa (ICOR: Journal of Regional Economics, 2025)
Education has a crucial role in the development of a nation, because the character, abilities and intelligence of a nation in the future will be greatly influenced by the education that exists today. GER, which is one of the benchmarks for educational attainment in South Sulawesi Province, has continued to decline over the last five years. These conditions are the background for this research. This research aims to determine the effect of the realization of the educational function budget per student, GRDP per capita, number of schools and number of teachers on the GER at elementary school (SD) level in South Sulawesi Province. This research uses a quantitative type of research. The data processing technique uses multiple linear regression with the help of the eviews 12 program. This model shows how much influence there is between the independent variable and the dependent variable using the OLS (Ordinary Least Square) approach. The data used is secondary data in the form of time series data for the period 2003-2022 obtained from published reports. The results of this research show that the realization of the educational function budget per student, GRDP per capita, and the number of teachers not significant effect on the GER at the elementary school (SD) level in South Sulawesi Province. Meanwhile, the number of schools has a significant effect but the relationship is negative on the GER at elementary school (SD) and equivalent levels in South Sulawesi Province. Keywords: Gross Enrollment Rate (GER), Realization of Education Function Budget per Student, GRDP per Capita, Number of Schools, Number of Teachers.